Π Complexes of P^P and P^N chelated gold(i). Issue 55 (21st June 2019) - Navarro, Miquel; Toledo, Alberto; Joost, Maximilian; Amgoune, Abderrahmane; Mallet-Ladeira, Sonia; Bourissou, Didier
Abstract : Tricoordinate gold(i ) π-complexes containing P-based chelating ligands (P^P and P^N) were prepared. Abstract : Tricoordinate gold(i ) π-complexes containing P-based chelating ligands (P^P and P^N) were prepared. The structure of the gold(i ) styrene complexes has been analysed in detail based on NMR and XRD data. The P^N complex is a competent catalyst for indole alkylation. The reaction proceeds with complete C3 and Markovnikov selectivity.